Organic cations directed 1D [Pb3Br10]4− chains: syntheses, crystal structures, and photoluminescence properties. Issue 2 (25th November 2020) - Jing, Chang-Qing; Li, Jing-Zhao; Xu, Te; Jiang, Kuan; Zhao, Xue-Jie; Wu, Yu-Fang; Xue, Nian-Ting; Jing, Zhi-Hong; Lei, Xiao-Wu
Abstract : To diversify the luminescence properties of 1D perovskites, different organic amine cations were combined with 1D [Pb3 Br10 ] 4− chains leading to a series of A2 Pb3 Br10 homologues, displaying broadband near white-light emissions with highest CRI of 96. Abstract : Recently, low-dimensional organic–inorganic hybrid metal halides have attracted considerable attention in solid-state optical application fields, especially in white-light emitting diodes (WLEDs) owing to intrinsic broadband luminescence performances. Herein, by selecting different types of organic cations as a structural decoration strategy, we designed a series of new 1D hybrid halides of A2 Pb3 Br10 (A = NPM, DMPDA, TMEN) based on same [Pb3 Br10 ] 4− chains composed of edge-shared [Pb3 Br12 ] 6− trimers. The low-dimensional crystal lattice results in the formation of self-trapped excitons, which leads to broadband light emissions covering the entire visible region for all A2 Pb3 Br10 homologues. Specifically, compound 1 exhibits yellowish-white light emission (0.34, 0.45) with a photoluminescence quantum efficiency of 2.51%. Both compounds 2 and 3 show bluish-white light emissions centered at 438 nm and 440 nm, respectively, with high color rendering index (CRI) of 96, which belongs to one of the highest values to date. The intrinsic broadband white light emissions enable them as promising candidates for single-component white-light emitting materials.